(Un)Curating COVID: Lessons from Corona in the City. (1st April 2022) - Schavemaker, Margriet; Schoutens, Esmee; Stol, Rowan
Shortly after the first lockdown in response to the COVID-19 pandemic in 2020, the Amsterdam Museum launched the online exhibition Corona in the City. The multimedia platform, which invites inhabitants of the city of Amsterdam to contribute their own stories, aims to collect the pandemic as it is experienced. The authors look back on the trajectory of the platform during its first year and observe how, through a combination of curating and 'uncurating' the content, the museum demonstrates a broader change in its policy towards collecting and storytelling. We reflect on ways in which the platform has and will change according to how the pandemic unfolds, and propose that it can serve as a pilot for more democratic, co-created institutions in the future.